Coping strategies and personal growth: The case of Palestinian refugees in Shatila camp, Lebanon - Al Beainy, Sara; El Hassan, Karma (Frontiers in Psychology, 2023)
This study investigated the relationship between coping strategies used by adolescent refugees in the Palestinian refugees’ Shatila camp in Lebanon and posttraumatic growth. Moreover, the study explored and predicted the impact of coping strategies utilized by adolescent Palestinians in Shatila camp, Lebanon on their personal growth and psychological well-being. Data were collected using two questionnaires and a checklist: (a) LEC-5 checklist as an assessment tool to make sure that all the participants have faced or experienced stressful events, (b) questionnaires including the Ways of Coping Questionnaire (WCQ) to find out the style of coping refugees used, and (c) Posttraumatic Growth Inventory (PTGI) to identify the factors of growth refugees developed as a result of using different coping strategies. Sixty adolescent refugees at one of the centers in the camp (31 females and 29 males) who benefited from counseling services participated in the study. Adolescent refugees’ performance on the checklist and questionnaires revealed the prevalence of stressors among the refugees. The coping strategies mostly utilized were problem-focused coping strategies, as there was a correlation between its factors and some coping strategies, and there were coping strategies used that predict the development of growth among. Finally, as for the counseling and training programs and services, interventions and guidance services seem to better prepare refugees to handle and cope with the stress that they encounter to develop personal growth.